PENINDAKAN BEA DAN CUKAI DALAM MELAKUKAN PENYIDIKAN TERHADAP PARA WISATAWAN ASING YANG MEMBAWA NARKOTIKA - Erwin Syahputra (Nusantara Hasana Journal, 2022)
The Directorate General of Customs and Excise is given the authority to supervise the export and import of goods without disturbing the smooth process of the tourists who come and is given the authority to take action if narcotics are found. In its application, the technical agency stipulates prohibition and restriction regulations and notifies the Minister of Finance of the Republic of Indonesia to be carried out by the Directorate General of Customs and Excise in the field of special supervision, of course it must be given to the entry of prohibited goods that can interfere with the life of the nation and state. Teluk Nibung Customs and Excise officers against tourists from Malaysia with the initials NZ who entered the port of Teluk Nibung with narcotics shabu. This legal research uses empirical legal research methods and conducts a case study at the Teluk Nibung Customs and Excise Office. This legal research uses primary legal materials, namely: Per Law. Secondary legal materials, namely: law books. Tertiary legal materials, namely: non-legal books. The process of action carried out by the Teluk Nibung Customs and Excise officers against foreign tourists who bring narcotics, namely an in-depth examination of the luggage and bodies of foreign tourists, tourists are taken to the Teluk Nibung Customs and Excise office for further inspection processes, laboratory tests are carried out Regarding the type of narcotics carried, the development of the narcotics carrier network with the North Sumatra Police Narcotics Unit or Tanjungbalai City Police along with the North Sumatra Province BNN or Tanjungbalai City BNN, goods and tourists are handed over to the police or to the National Narcotics Agency. The external obstacle is the occurrence of language differences as for the solutions faced by establishing good interactions with foreign tourists.